Effect of hormones on in vitro culture of Sesame Sesamum indicum (L.) embryo - Morenike Jayeoba, Feyiropo; Toyin Mustapha, Oba (Research in Biotechnology, 2014)
The in vitro response of three Sesame Sesamum indicum L. genotypes, Alaede, E8 and Ex Sudan obtained from NCRI, Badeggi, Nigeria was studied using tissue culture techniques. Growth media with different concentrations and combinations of hormones were used for callus induction, shoot formation from callus subculture and plantlets development from leaf subculture. Ex Sudan recorded the highest callusing frequency at 0.25mg*L-1 2, 4 D + 0.08mg*L-1 Kinetin. It also recorded the highest shoot formation frequency on full strength MS media only and produced the highest mean in seedling development from sub cultured leaves at 0.1mg*L-1 Kinetin + 0.2mg*L-1 NAA and 0.3mg*L-1 Kinetin + 0.1mg*L-1 2,4 D. The latter concentration showed significant difference among the three genotypes. Ex Sudan was found to be more suitable for tissue culture procedures as a result of its responses to the treatments administered, and stand as a candidate for improvement of the other local varieties.